Організація і проведення слухань у комітетах Верховної Ради України. - Словська, І.Є.; Словская, И.Е.; Slovskaja, I (My University, 2012)
Author characterizes organization procedure and hearings conducting in parliament of Ukraine committees according to current legislation, probes the value of listening for a state creative process and offers possible ways for actual constitutionally legal institute improvement.
Словська І.Є. Організація і проведення слухань у комітетах Верховної Ради України. / І.Є.Словська //Актуальні проблеми політики : зб. наук. пр. / гол. ред. С. В. Ківалов ; відп. за вип. Л. І. Кормич. – Одеса : Національний університет "Одеська юридична академія" : Південноукраїнський центр гендерних проблем, 2012. – Вип. 44. – C. 211 - 219.
Keywords: Удосконалення конституційно - правового інституту; Комітети Верховної Ради; Організація і проведення слухань у Верховній Раді; Дослідження процедури слухань за чинним законодавством; Парламентський контроль; Парламентский контроль; Исследование процедуры слушаний в Верховной Раде; Организация и проведение слушаний в Верховной Раде; Комитеты Верховной Рады; Усовершенствование конституционно - правового института; Improvement of the constitutional - legal institution; The committees of the Verkhovna Rada; Organization and holding of hearings in the Verkhovna Rada; nvestigation procedures hearings in the Verkhovna Rada; Parliamentary control